1989
DOI: 10.1007/bf00930977
|View full text |Cite
|
Sign up to set email alerts
|

Proteins ofNippostrongylus brasiliensis analyzed by immunoblotting

Abstract: Antigenic proteins were characterized by the immunoblotting technique with sera from rats and mice after infection as well as hyperimmune sera. The immune response of infected animals was mainly directed toward five proteins of adult worms (190, 118, 110, 98, and 52 kDa) and four proteins of the third larval stage (L3; 92, 78, 58, and 24 kDa). The immunoblots indicated that stage-specific proteins of the homogenates were recognized. Three stage-specific proteins of L3 larvae (150, 135, and 125 kDa) and three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, there is a paucity of evidence relating the exposure of hosts to somatic molecules from nematodes, and it is very reasonable to assume that somatic products from dead or dying worms can influence the host. Indeed, antibodies to somatic antigens are found in a variety of nematode infections, thus confirming exposure to somatic products in these infections (11,24,32,44).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, there is a paucity of evidence relating the exposure of hosts to somatic molecules from nematodes, and it is very reasonable to assume that somatic products from dead or dying worms can influence the host. Indeed, antibodies to somatic antigens are found in a variety of nematode infections, thus confirming exposure to somatic products in these infections (11,24,32,44).…”
Section: Discussionmentioning
confidence: 84%
“…It is possible that the stage-specific expression of the immunomodulatory factor could be an adaptation by the adult nematode to immunosuppress the host during the critical egg-producing stage. This shift in protein composition as nematodes develop from larvae to adults has been well documented, including in the nematode N. brasiliensis (11,24,32). Because the extract used in this study is a whole-worm homogenate, we do not know if the modulatory factor is secreted (thus raising the question of clinical relevance).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the results with individual antigen fractions bound to nitrocellulose it is shown that only a small num ber of antigens increased the IgE production. As wc dem onstrated in previous experiments IgE antibodies reacted only with proteins of the WH [12]. A comparison of the immunoblot analysis with the results obtained by the cell cul tures incubated with antigen fractions suggests that the IgE-binding and the IgE-cnhancing fractions belong to the same molecular weight ranges.…”
Section: Discussionmentioning
confidence: 84%
“…It was the purpose of our investigations to analyze the influ ence of soluble N.b. antigens previously characterized by immunoblotting [12] in the presence or absence of cyto kines in T/B cell cocultures as well as Transwell cultures.…”
Section: Introductionmentioning
confidence: 99%